Bic Runga's Drive - Johnson, Henry (Bloomsbury Academic, 2023)
"Discusses Bic Runga's Drive as the foundation for launching her career as an icon of New Zealand popular music"--
Keywords: Runga, Bic -- 1976-; Geschichte 1997; Musikalbum; Runga, Bic / 1976- / Drive; Popular music / New Zealand / 1991-2000 / History and criticism; Popular music; New Zealand; 1991-2000; Criticism, interpretation, etc